Law of effect models and choice between many alternatives - Navakatikyan, Michael Alexander; Murrell, Paul; Bensemann, Joshua; Davison, Michael; Elliffe, Douglas (Journal of the experimental analysis of behavior, 2013)
Data from five experiments on choice between more than two variable‐interval schedules were modeled with different equations for the Law of Effect. Navakatikyan's (2007) component‐functions models with three, four and five free parameters were compared with Stevens' (1957), Herrnstein's (1970) and Davison and Hunter's (1976) equations. These latter models are consistent with the generalized‐matching principle, whereas Navakatikyan's models are not. Navakatikyan's models performed better or on par with their competitors, especially in predicting residence‐time data and generalized‐matching sensitivities for time allocation. The models described well an observed decrease, in several of these data sets, in generalized‐matching sensitivity between two alternatives when reinforcer rate increased on the other alternatives. Models built on the generalized‐matching principle cannot do this. Navakatikyan's models also performed better, though to a lesser extent, than their competitors for data sets that are not obviously inconsistent with generalized matching.